Journalistic approaches to the problems of indigenous groups in Costa Rica’s written media - Ureña García, Óscar (2019)
The Costa Rican press has for many years addressed indigenous issues in adistorted way. They assume a vision as if the Costa Rican natives were notpart of the country and their realities did not exist and, when approached, theyfocus the protagonism on the non-indigenous. This paper clearly shows andanalyzes that distorted view that is created from the journalistic approachesin the national printed and digital media of greater reach in Costa Rica.